Kebijakan Kriminal Terhadap, Gay, Biseksual Dan Transgender (LGBT) Dikaitkan Dengan Delik Kesusilaan Di Dalam Kitab Undang-Undang Hukum Pidana - Ateng Sudibyo (DE LEGA LATA: JURNAL ILMU HUKUM, 2019)
The presence of LGBT groups in Indonesia has in fact caused a stir in Indonesian society, because it has been regarded as a resistance to religion, nature, and values that live in Indonesian society which has never allowed such acts. LGBT acts are acts that violate the rules of religion and the value of religious life in Indonesian society. But ironically there is no legal umbrella specifically to regulate the LGBT problem even though if it is viewed from the illegal nature of an act, even if the act is not regulated in laws and regulations (against formal law), but if the deed is considered despicable because justice or norms of social life in society (against material law) then the action can be punished. The purpose of this study is to find out the legislation policy on LGBT in the offense of decency of the Criminal Code and to formulate the concept of LGBT criminal policy in decency offenses of the Law Future Criminal Law in Indonesia. This study uses a normative juridical approach and the nature of this research is descriptive analytical. Data retrieval is done through library studies in order to obtain secondary data, both in the form of primary legal materials, secondary legal materials, and tertiary legal materials. To support the research that has been carried out, field research is also carried out in order to obtain primary data that supports secondary data. The technical analysis used in this study is a qualitative analysis technique.